THE SELF AND THE EVERYDAYNESS - Nerijus Milerius (Problemos)
The article deals with the problem of the self and the everyday world. In the history of philosophy, the problem of the everydayness has been neglected and rarely met in question, but it is theories of knowledge of the New Ages which have fully excluded the possibility of the refferense to the everydayness. As axamples of that approach, the notions of the subject and the world in the philosophical theories of R. Descartes, V. G. Leibniz and I. Kant are briefly exposed. It is argued that early L. Wittgenstein transforms the kantian question of the conditions of the possibility of the knowledge into that of the conditions of the possibility of the language, but, at the same time, introduces the notion of the showing which could lead to the understanding of the thinking as attentivity. It is showed that namely on the base of the attentivity the problems of the self and the everyday world could be conected and mutually described. Finally, it is concluded that despite the permanent philosophical ambition to present the description of the self and the everydayness in the systematical way, the philosophy based on the attentivity sometimes requires the love or some instances of the silence rather than the systematical approasch to the self and to the world.